Hunting for second copy of GRB10 interacting gyf domain (GIGYF) family genes in danio rerio genome - Foong, Pik Mun (Universiti Malaysia Sarawak, UNIMAS, 2010)
Grb10 Interacting GYF domain (GIGYF) family genes consist of two members, namely GIGYF1 and GIGYF2 respectively. These two genes have been found to have interaction with Grb10 and Insulin-like Growth Factor I (IGF-I) as well as the insulin receptor. Further studies had shown that mutation of GIGYF2 in the PARK 11 locus might causes development of familial Parkinson’s disease (PD). Therefore, the aim of this study is to identify a second copy of GIGYF genes from the genome of Danio rerio (zebrafish), in which the first copy has been accomplished by Lee in year 2008. The presence of another copy would suggest the occurrence of genome duplication in zebrafish, and this would enable further study of the gene, especially in determine its mutational effect on PD. In this study, two copies of GIGYF1 genes have been found in LG7 and 10 respectively, while single copy of GIGYF2 was identified in LG2, which is designed as the original copy. BLAST search result is however, showed high possibility of second copy of GIGYF2 in the genome. Subsequent phylogenetics analysis suggested the evolutionary relationship between zebrafish and the homologous species. Paralogous relationship was identified between the two GIGYF1 copies. The three-dimensional structures of GIGYF family genes have been constructed through homology modelling using 3D-Jigsaw, and composite modelling through I-TASSER. The models are sent for function prediction and annotation. Further researches are recommended to perform verification study through experimental approaches.